Perlindungan Hukum Rahasia Dagang Terhadap Produk Skincare Home Industry - Wellastry Yamin; Ronald Saija; Sarah Selfina Kuahaty (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The high interest of skincare home industry products has made these product business actors mushrooming in almost all e-commerce platforms.Purposes of the Research: The purpose of this research is to examine and discuss the legal protection of intellectual property rights for skincare home industry products.Methods of the Research: This research was conducted with a normative juridical research type using a statute approach. To answer the existing problems, the author collects legal materials through literature studies and analyzes them using qualitative analysis methods.Results of the Research: The results of this research indicate that the legal protection that can be obtained by skincare home industry product owners in the field of trade secrets is related to confidential information that has commercial value, related to production, processing, sales, or other technical and/or economic information that has economic value and is unknown in general in the manufacture of these products. Then, the form of legal protection can be in the form of making a written agreement based on a consulting contract as a legal effort to protect his trade secrets, as well as filing a claim for compensation, using alternative dispute resolutions, and/or filing criminal charges, if there has been a violation.